Balancing Tradition and Modernity: Evaluating the Impact of Pesantren Leadership on Curriculum Transformation Outcomes - Iskandar Iskandar; Anjas Baik Putra; Minhajul Abidin Mank; Cittra Juniarni; Talita Afifah Husni (Idarah (Jurnal Pendidikan dan Kependidikan), 2024)
The importance of pesantren growth has not been matched by improvements in the quality of pesantren education services. One of the policies focuses produces a transformation of the pesantren curriculum. This study will examine at how tradition and modernity interact in the pesantren curriculum management system. The study was conducted in two pesantren in Aceh Tengggara, Darul Amin and Darul Azhar. The research methodology was qualitative, with a descriptive survey technique. Data were gathered from seven informants, including the leader, curriculum deputy, and several pesantren teachers. The research data was analyzed using a data comparative model. The findings demonstrated the efficacy of combining traditional management with contemporary management, with a focus on improving the core of pesantren education services, specifically the pesantren curriculum. The identification of Buya Pesantren's leadership style results in transformative and charismatic leadership styles. The process of curriculum transformation culminates in an integrative pattern between the dayah-salafy-KMI curriculum. The curriculum transformation policy is also implemented through extracurricular activities aimed at improving Santri's soft and hard skills. While learning is conducted instructionally and in accordance with technological advancements, the selection of learning materials is broad in scope. The findings have implications for santri skills and competitiveness in society, particularly in the workplace.